2018
DOI: 10.3390/vaccines6030052
|View full text |Cite
|
Sign up to set email alerts
|

Next Generation Cancer Vaccines—Make It Personal!

Abstract: Dramatic success in cancer immunotherapy has been achieved over the last decade with the introduction of checkpoint inhibitors, leading to response rates higher than with chemotherapy in certain cancer types. These responses are often restricted to cancers that have a high mutational burden and show pre-existing T-cell infiltrates. Despite extensive efforts, therapeutic vaccines have been mostly unsuccessful in the clinic. With the introduction of next generation sequencing, the identification of individual mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 106 publications
0
16
0
Order By: Relevance
“…The immunosuppressive TME is a major cause for failure of cancer vaccine immunotherapy (20). Therefore, we next examined whether codelivery of PD-L1 siRNA and IL-2 pDNA could modulate the immunosuppressive TME to restore the efficacy of a tumor vaccine in HCC.…”
Section: Pd-l1 Sirna and Il-2 Pdna Codelivered By Tt-ldcp Nps Reprogrmentioning
confidence: 99%
“…The immunosuppressive TME is a major cause for failure of cancer vaccine immunotherapy (20). Therefore, we next examined whether codelivery of PD-L1 siRNA and IL-2 pDNA could modulate the immunosuppressive TME to restore the efficacy of a tumor vaccine in HCC.…”
Section: Pd-l1 Sirna and Il-2 Pdna Codelivered By Tt-ldcp Nps Reprogrmentioning
confidence: 99%
“…These patients will require an induction or direct administration of tumor-specific T cells in order for the cells to reach the tumors [104]. Recent studies suggested that neoantigens, which arise as a result of genetic mutations in the tumor, can effectively eliminate tumor cells [105,106]. However, neoantigens are not suited for use as universal antigens because they differ among patients and cancer types.…”
Section: Htert-targeted Cancer Immunotherapy: Future Perspectivesmentioning
confidence: 99%
“…In contrast to the above strategies, tumor vaccines, which are designed to expand tumor-specific T-cell responses through enhanced active immunization, have long been anticipated as probable effective cancer immunotherapy [ 20 , 21 ]. The antigen categories of the tumor vaccines are varied [ 22 , 23 ], among which, whole tumor cell-based vaccines have been employed in numerous studies over the past decade, which can offer several advantages over subunit and peptide vaccines [ 24 , 25 ], and hundreds of them were tested in clinical trials to date [ [26] , [27] , [28] ]. Repeated freeze-thaw and irradiation methods are commonly used to prepare whole tumor cell vaccines [ 29 ].…”
Section: Introductionmentioning
confidence: 99%